Temporal Trends in Pollination Deficits and Its Potential Impacts on Chinese Agriculture - Mashilingi, Shibonage K. (2021)
Fil: Mashilingi, Shibonage K. Chinese Academy of Agricultural Sciences. Institute of Apicultural Research. Key Laboratory for Insect-Pollinator Biology of the Ministry of Agriculture and Rural Affair. China.